Development of an Interdisciplinary Telehealth Model of Provider Training and Comprehensive Care for Hepatitis C and Opioid Use Disorder in a High-Burden Region. (2nd September 2020) - Sherbuk, Jacqueline E; Knick, Terry Kemp; Canan, Chelsea; Ross, Patrice; Helbert, Bailey; Cantrell, Eleanor Sue; Cantrell, Charlene Joie; Stallings, Rachel; Barron, Nicole; Jordan, Diana; McManus, Kathleen A; Dillingham, Rebecca
Abstract: Background: Hepatitis C virus (HCV) and the opioid epidemic disproportionately affect the Appalachian region. Geographic and financial barriers prevent access to specialty care. Interventions are needed to address the HCV-opioid syndemic in this region. Methods: We developed an innovative, collaborative telehealth model in Southwest Virginia featuring bidirectional referrals from and to comprehensive harm reduction (CHR) programs and office-based opioid therapy (OBOT), as well as workforce development through local provider training in HCV management. We aimed to (1) describe the implementation process of provider training and (2) assess the effectiveness of the telehealth model by monitoring patient outcomes in the first year. Results: The provider training model moved from a graduated autonomy model with direct specialist supervision to a 1-day workshop with parallel tracks for providers and support staff followed by monthly case conferences. Forty-four providers and support staff attended training. Eight providers have begun treating independently. For the telehealth component, 123 people were referred, with 62% referred from partner OBOT or CHR sites; 103 (84%) attended a visit, 93 (76%) completed the treatment course, and 61 (50%) have achieved sustained virologic response. Rates of sustained virologic response did not differ by receipt of treatment for opioid use disorder. Conclusions: Providers demonstrated a preference for an in-person training workshop, though further investigation is needed to determine why only a minority of those trained have begun treating HCV independently. The interdisciplinary nature of this program led to efficient treatment of hepatitis C in a real-world population with a majority of patients referred from OBOTs and CHR programs.